Collection and evaluation of Cumulus-Oocyte Complexes (CoCS) from goat slaughterhouse ovary in view of in vitro production of embryo - Nur Ariani Dzulkarnain (2016)
The evaluation of ovaries, efficient collection and grading the cumulus oocyte complexes (COCS) is the initial step involve in the production of embryo in vitro. The objectives of this study were to evaluate the ovaries and recovery rate of COCS from goat slaughterhouse ovary and to find out the relationship between the number of follicles dissected and cumulus oocyte complexes (COCS) recovery. From the observation of the ovarian types, it was found that 100% of ovaries were to ovary without CL group. In each and every ovarian surface, the number of visible follicles was counted and the follicles were collected by blunt dissection technique. Via blunt dissection, scissors and forceps were used to dissect individual follicles from the ovaries, and then the follicular materials were harvested individually in the culture dish. The follicular materials collected was observed under microscope to categorize the COCs as grade A (oocyte homogenously surrounded with cumulus cells), grade B (oocyte partially surrounded with cumulus cells), grade C (oocyte not surrounded at all with cumulus cells) and grade D (degeneration observed both in oocyte and cumulus cells). Grade A and grade B were considered as normal COCs while grade C and grade D were considered as abnormal COCs. The results were analysed using mean ± SE with the help of Microsoft Office Excel 2013. From the total of 159 visible follicles, 117 follicles were able to be dissected. Among the follicles dissected, the total 66 COCs collected and classified into two groups; normal (Grade A and B) group and abnormal (Grade C and D) group. It shows that all the visible follicles not able to be dissected which is normal. However, the number of normal COCs per ovary (4.9 ± 0.6) observed is higher than the number of abnormal COCs per ovary (1.7 ± 0.6). The average recovery rate of COCs per ovary was 56.7 %. From the total, the recovery rate for the normal COCs (42.4 %) was higher than the recovery rate for the abnormal COCs (14.3 %). The COCs recovery increased as the number of follicle dissected increased which reflected that higher number of follicles positively effected on the increasing of COCs recovery. From this study, it can be concluded that only the non-cyclic female goat were slaughtered in the slaughterhouse. Mostly, the non-reproductive performing animals were slaughtered which increase the possibility to get the non-cyclic ovaries from the slaughterhouse during the sample collection and remarkable number of normal COCs is possible to collect by blunt dissection technique to initiate the in vitro production of embryo experiment.